The paradox of promoting creativity in the Asian classroom: An empirical investigation - NG, Aik Kwang (Institutional Knowledge at Singapore Management University, 2004)
To shed light on the paradox of promoting creativity in the Asian classroom, the authors conducted 3 studies. The 1st study found that novice teachers classified student behaviors as desirable but uncreative (DBU) versus creative but undesirable (CBU). The 2nd study found that conservative-autocratic teachers were more likely to encourage DBU behaviors in class, whereas liberal-democratic teachers were more likely to encourage CBU behaviors in class. The 3rd study found that cultural individualism—collectivism had a positive impact on liberal—democratic teaching attitude but a negative impact on conservative—autocratic teaching attitude. In turn, liberal—democratic teaching attitude had a positive impact on the tendency to promote CBU behaviors, whereas conservative—autocratic teaching attitude had a positive impact on the tendency to promote DBU behaviors.